The role of human capital in the growth of the Iraqi economy (for the period 1980-2016) - Khalid Haider; Faisal Ali Khurshid (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
The human capital is the most important factor influencing the economic growth in any country. And according to that, in the last four decades, governments and policy makers in developed and developing countries have focused on this factor. In experimental studies, government expenditure on education and health is used to determine the role of the human capital in this growth. Therefore, this research attempts to analyze the role of human capital (education and health) in the growth of the Iraqi economy for the period (1980 - 2016). The ARDL model was used to analyze this role on the short and long term. The results of the research indicate the positive role of human capital in economic growth in both terms. Key words: human capital, human capital expenditure, economic growth, GDP per capita, ARDL model.